2015
DOI: 10.1002/chem.201500033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanofluorochromic Materials Based on Aggregation‐Induced Emission‐Active Boron Ketoiminates: Regulation of the Direction of the Emission Color Changes

Abstract: We report a series of mechanofluorochromic (MFC) compounds based on organoboron complexes with aggregation-induced emission (AIE) characteristics. We synthesized a variety of boron ketoiminates and investigated the effect of the substituents on the optical properties by altering the end groups in the compounds. The synthesized boron ketoiminates showed AIE properties and MFC behavior. Interestingly, the hypsochromic and bathochromic shifts of the emission bands individually observed for boron ketoiminates depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(71 citation statements)
references
References 38 publications
2
69
0
Order By: Relevance
“…The series of triads composed of two boron ketoiminates and a central bithiophene unit with various functional groups at both ends were synthesized ( Figure 12). 93 As we expected, these triads provided solid-state emission. Interestingly, the emission colors were clearly changed upon grinding the crystalline sample powders to the point the X-ray diffraction peaks disappeared.…”
Section: Progress In the Development Of Advanced Element-block Materisupporting
confidence: 64%
“…The series of triads composed of two boron ketoiminates and a central bithiophene unit with various functional groups at both ends were synthesized ( Figure 12). 93 As we expected, these triads provided solid-state emission. Interestingly, the emission colors were clearly changed upon grinding the crystalline sample powders to the point the X-ray diffraction peaks disappeared.…”
Section: Progress In the Development Of Advanced Element-block Materisupporting
confidence: 64%
“…49 A variety of boron ketoiminates with diverse substituent groups at both ends were synthesized, and the substituent effects on the optical properties were investigated. Similar to above, boron ketoiminates exhibited AIE properties.…”
Section: Emissive Solid Materials Based On the Aie Propertymentioning
confidence: 99%
“…This was attributed to intermolecular interactions, such as halogen−halogen bonding, not present in non-halogensubstituted dyes. 44 Though ML materials have potential for practical applications, logical design of these materials remains challenging. 1,2 Prior work in our group has demonstrated that reversible ML properties of BF 2 bdk dyes bearing alkyl chain substituents are highly dependent on the length of the chain, and thus, their properties can be tuned by varying chain length.…”
Section: ■ Introductionmentioning
confidence: 99%